The Influence of Electoral Oversight Management Factors on Public Perception through Public Trust in the 2024 Simultaneous Elections in Ngawi Regency - Anita Setia Mega Putri; Muslichah Erma Widiana; Nurul Qomari; Juliani Pudjowati (Journal of Economics and Social Sciences (JESS), 2026)
Electoral oversight plays a crucial role in safeguarding electoral integrity and strengthening democratic legitimacy, particularly in emerging democracies where public trust in electoral institutions remains a central challenge. This study aims to examine how electoral oversight management influences public perception through the mediating role of public trust in the 2024 Simultaneous Elections in Ngawi Regency, Indonesia. Employing a quantitative explanatory research design, the study analyzed the effects of four dimensions of electoral oversight management—planning, organizing, implementation, and evaluation—on public trust and public perception. Data were collected from 400 registered voters selected through proportional stratified random sampling and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings reveal that electoral oversight organizing has a direct and significant effect on public perception, while planning, implementation, and evaluation do not exert significant direct effects. However, organizing, implementation, and evaluation significantly influence public trust, whereas planning does not. Public trust is found to have a positive and significant effect on public perception and serves as a mediating variable in the relationships between organizing, implementation, and evaluation of oversight and public perception. Conversely, public trust does not mediate the relationship between oversight planning and public perception. These results indicate that public perception of electoral oversight is shaped primarily by oversight practices that are visible, organized, accountable, and directly experienced by the public, with public trust functioning as the key mechanism linking oversight performance to societal evaluations. The study contributes to the literature on electoral governance by highlighting the strategic role of public trust in translating managerial performance into positive public perception at the local level.